Application of a Convective-Conductive Heat Transfer Model in the Heat Loss Analysis of a Heat Pipeline Under Flooding Conditions; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Polovnikov V. Yu. Vyacheslav Yurievich (2016, 2016)
Title screen